GRAFENO INTERAGINDO COM MOLÉCULAS DE RESVERATROL E QUERCETINA VIA MODELAGEM MOLECULAR - Hartmann, Julio Henrique (2014)
In this work we examined theoretically via computer simulation of first principles, the interaction of graphene with the molecules of resveratrol and quercetin. To do this, use the Density Functional Theory and the pseudopotential method as implemented in the SIESTA computer code. Resveratrol is an antioxidant drug and several studies have highlighted and proven the benefits of resveratrol health. This has been shown flavonoid chemopreventive, antioxidant, antiplatelet, antifungal, anti-inflammatory, cardioprotective, among others. Quercetin is the main flavonoid present in the human diet and its therapeutic properties have been studied in recent decades, highlighting the potential antioxidant, anticarcinogenic and its protective effects on renal, cardiovascular and hepatic systems, and also has antimicrobial activity. However, these two drugs are very unstable. In this regard, the main motivation is to use graphene with these two drug molecules to overcome the instability of the same, because of the properties of graphene Its primary is exactly be electrochemically stable. Our results show that the most stable configuration for the binding energy of quercetin with graphene was 0.93 eV and resveratrol value found for the binding energy was 0.53 eV indicating the occurrence of weak interaction through physical adsorption. Analyzing the band structure of the interacting systems, we found that no significant changes occur in the electronic properties compared to pure graphene. The stability of the molecules was improved due to charge transfer and the decrease of the total energy of the molecules.